Threaded harmony : a sustainable approach to fashion - Rana, Nirbhay (Emerald points., 2024)
Fashion, a realm often associated with trends and whims, is undergoing a transformation--one that goes beyond aesthetics to embrace sustainability as a guiding principle. Threaded Harmony: A Sustainable Approach to Fashion is a journey into this transformative realm, an exploration of how consumers can impact the industry and how the industry can align with environmental and social responsibility while fostering creativity and innovation. Threaded Harmony acts as a comprehensive guide exploring the urgent need for sustainability in the fashion industry. Author Nirbhay Rana delves into the environmental impact of fashion, discussing the ecological footprint of fast fashion, pollution, and waste in the supply chain, supported by real-life case studies. He emphasizes the philosophy of "Threaded Harmony," advocating for a balanced and sustainable approach. Chapters cover various aspects of sustainable fashion, from understanding eco-friendly materials like organic cotton, hemp, and bamboo to exploring ethical fashion practices such as fair trade, workers' rights, and empowering local communities. The work also explores the circular fashion economy, promoting reducing, reusing, and recycling, along with the importance of a slow fashion movement that encourages mindful consumerism and personal style expression over trends. Whether you are a seasoned fashion enthusiast, a conscious consumer, or an academic investigating the sustainable fashion movement, this work invites you to explore, question, and reimagine the role of fashion in our lives.